A computational approach to sequential decision optimization in energy storage and trading - Paolo Falbo; Juri Hinz; Piyachat Leelasilapasart; Cristian Pelizzari (Journal of Risk and Financial Management, 2021)
Due to recent technical progress, battery energy storages are becoming a viable option in the power sector. Their optimal operational management focuses on load shift and shaving of price spikes. However, this requires optimally responding to electricity demand, intermittent generation, and volatile electricity prices. More importantly, such optimization must take into account the so-called deep discharge costs, which have a significant impact on battery lifespan. We present a solution to a class of stochastic optimal control problems associated with these applications. Our numerical techniques are based on efficient algorithms which deliver a guaranteed accuracy.
Keywords: 330; approximate dynamic programming; energy trading; optimal control; power sector